Abrupt climate change in the Atlantic Ocean during the last 20,000 years : insights from multi-element analysis of benthic and planktic foraminifera and coupled OA-GCM - Came, Rosemarie Evangeline (Massachusetts Institute of Technology, 2005)
Thesis (Ph. D.)--Joint Program in Oceanography/Applied Ocean Science and Engineering (Massachusetts Institute of Technology, Dept. of Earth, Atmospheric, and Planetary Sciences; and the Woods Hole Oceanographic Institution), 2005. Includes bibliographical references. Minor and trace element records of planktic and benthic foraminifera from Atlantic sediment cores, as well as output from a coupled OAGCM, were used to investigate the magnitude and distribution of the oceanic response to abrupt climate events of the past 20 kyr. The study addressed three major questions: 1) What is the magnitude of high-latitude sea surface temperature and salinity variability during abrupt climate events? 2) Does intermediate depth ventilation change in conjunction with high-latitude climate variability? 3) Are the paleoclimate data consistent with the response of a coupled OAGCM to a freshwater perturbation? To address these questions, analytical methods were implemented for the simultaneous measurement of Mg/Ca, Zn/Ca, Cd/Ca, Mn/Ca and Al/Ca in foraminiferal samples using inductively-coupled plasma mass spectrometry. Paired records of planktic foraminiferal [delta]¹⁸O and Mg/Ca from the subpolar North Atlantic reveal trends of increasing temperatures ([approx.] 3⁰C) and salinities over the course of the Holocene, which were punctuated by abrupt events. The variability does not appear to be periodic, but tends to recur within a broad millennial band. The records provide the first evidence of open-ocean cooling (nearly 2⁰C) and freshening during the 8.2 kyr event, and suggest similar conditions at 9.3 ka. (cont.) However, the two largest temperature oscillations ([approx.] 2⁰C) occurred during the last 4,000 years, suggesting a recent increase in temperature variability relative to the mid-Holocene. Benthic foraminiferal Cd/Ca from an intermediate depth, western South Atlantic core provides insights into changes in the southward penetration of North Atlantic Intermediate Water (NAIW). Cd seawater estimates (Cdw) for the last ...